2018
DOI: 10.1073/pnas.1814521115
|View full text |Cite
|
Sign up to set email alerts
|

PCNA-mediated stabilization of E3 ligase RFWD3 at the replication fork is essential for DNA replication

Abstract: RING finger and WD repeat domain-containing protein 3 (RFWD3) is an E3 ligase known to facilitate homologous recombination by removing replication protein A (RPA) and RAD51 from DNA damage sites. Further, RPA-mediated recruitment of RFWD3 to stalled replication forks is essential for interstrand cross-link repair. Here, we report that in unperturbed human cells, RFWD3 localizes at replication forks and associates with proliferating cell nuclear antigen (PCNA) via its PCNA-interacting protein (PIP) motif. PCNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 33 publications
3
35
0
2
Order By: Relevance
“…RFWD3 mutant cells exhibit increased foci of RPA and RAD51 when treated with MMC (Feeney et al 2017). Consistent with these observations, RFWD3 localizes to replication forks in a proliferating cell nuclear antigen (PCNA)-dependent manner (Lin et al 2018). In addition, RFWD3 is phosphorylated by the DNA damage response kinase ATR (and possibly ATM) (Fu et al 2010;Feeney et al 2017), and this may be required for its function.…”
supporting
confidence: 57%
“…RFWD3 mutant cells exhibit increased foci of RPA and RAD51 when treated with MMC (Feeney et al 2017). Consistent with these observations, RFWD3 localizes to replication forks in a proliferating cell nuclear antigen (PCNA)-dependent manner (Lin et al 2018). In addition, RFWD3 is phosphorylated by the DNA damage response kinase ATR (and possibly ATM) (Fu et al 2010;Feeney et al 2017), and this may be required for its function.…”
supporting
confidence: 57%
“…Furthermore, elongated strands of repeat five appear to be a feature unique to RFWD3 (Figure B panel iv). Interestingly, residues involved in DDR are not part of these insertions, including Trp‐543 and Ile‐639 for binding RPA32, and the QKMDF 624 consensus motif that mediates the interaction with PCNA (proliferating cell nuclear antigen) during DNA replication …”
Section: Resultsmentioning
confidence: 99%
“…2,3 Evidence has shown that the WDR domain is primarily responsible for the functional interactions that allow RFWD3 to maintain genomic stability. 4,5 Furthermore, heritable mutations, particularly an Ile639Lys point mutation within the WDR domain, may lead to the rare genomic instability disease known as Fanconi anemia (FA), 6 thereby implicating RFWD3 as a potential FA-associated gene (alias: FANCW). [4][5][6] Until recently, the biochemical characterization of RFWD3 has lacked complementary highresolution structural information.…”
mentioning
confidence: 99%
See 2 more Smart Citations